МЕТОД ВИЗНАЧЕННЯ ПРОСТОРОВОЇ ФОТОСИНТЕЗНОЇ ОПРОМІНЕНОСТІ - Червінський, Л.С.; Усенко, С.М.; Книжка, Т.С.; Луцак, Я.М. (Інститут електродинаміки НАН України, Київ, 2016)
Based methods of calculation fotosintesis irradiance at the level of plant leaves, which takes into account additional radiation reflected by the surface of the walls and ceiling. An example of using this method to determine the actual fotosinteznoi irradiation in greenhouses workplace with pictures that reflect the spatial distribution of the irradiance in the horizontal plane at the level of the leaves of plants. References 6.